Hyperoxia increases arterial oxygen pressure during exercise in type 2 diabetes patients: a feasibility study. Issue 1 (December 2016) - Rozenberg, Robert; Mankowski, Robert; Loon, Luc; Langendonk, Janneke; Sijbrands, Eric; Meiracker, Anton; Stam, Henk; Praet, Stephan
Abstract Objective The study investigated the feasibility and potential outcome measures during acute hyperoxia in type 2 diabetes patients (DM2). Methods Eleven DM2 patients (7 men and 4 women) were included in the study. The patients cycled (30 min at 20 % Wmax ) whilst breathing three different supplemental oxygen flows (SOF, 5, 10, 15 L min−1 ). During hyperoxic exercise, arterial blood gases and intra-arterial blood pressure measurements were obtained. Results Arterial pO2 levels increased significantly (ANOVA, p  < 0.05) with SOF: 13.9 ± 1.2 (0 L min−1 ); 18.5 ± 1.5 (5 L min−1 ); 21.7 ± 1.7 (10 L min−1 ); 24.0 ± 2.3 (15 L min−1 ). Heart rate (HR) and pH increased significantly after terminating administration of hyperoxic air. Conclusions An SOF of 15 L min−1 appears to be more effective than 5 or 10 L min−1 . Moreover, HR, blood pressure, blood lactate and pH are not recommended as primary outcome measures.